The Dark Spirit of the Trickster Archetype in Parapsychology - Storm, Lance (Journal of Scientific Exploration, 2023)
In this paper, the phenomenology of the Trickster (its ‘darker’ side) is explored. The archetypal Trickster is shown to manifest as psychosociological aberrations and bizarre physical effects often associated with unique individuals during certain emotionally charged states. Though the Trickster and its many variants have mythological roots, the modern-day equivalent (free, for example, from anthropomorphization) can be seen as an activated psychological proneness to err in thinking when a liminal phase is entered into—that borderland between doubt and certainty. Mainstream academia considers the field of parapsychology to be controversial—it is marginalized because the phenomena it studies (the paranormal) is mostly illusive, usually weak even when proved to be statistically anomalous, and the psi process itself has not been theoretically explained. This state of affairs propagates uncertainty which can trigger ‘tricksterish’ (spurious) interpretations of parapsychological data and findings: Long-term experimenter psi and chronological decline effects are cases in point. Due caution and bias-free analysis of the data and findings may help ameliorate, perhaps even dissolve, the problem of the Trickster.